HARAPAN VS REALITAS: STUDI WALI ADHAL DI PENGADILAN AGAMA SLEMAN PERSPEKTIF SOSIOLOGI HUKUM ISLAM - Nurin Fitria, Halla; Ibrahim, Malik; Handayani, Dwi (Al-Iqro', 2025)
Wali adhal or reluctant guardian can be explained as a wali nasab who refuses to allow the marriage of the bride-to-be. Because of this refusal, the bride-to-be had to file a case with the local religious court. This application was filed to ask the judge to appoint a guardian in place of the guardian who refused. The Sleman Religious Court, in the context of the Yogyakarta Special Region Province, recorded the highest number of guardian petitions from 2019 to 2021. This study aims to analyze the sociological factors of Islamic law behind court decisions related to the case of wali adhal number 104/Pdt.P/2021/PA. Smn at the Sleman Religious Court. This research uses a qualitative approach that combines field research, interviews, and literature research. The approach used is the approach of the sociology of Islamic law. The result of the determination of the case of the guardian adhal number 104/Pdt.P/2021/PA. Smn revealed that the judge considered factors such as the absence of shari'i barriers to marriage and the reasons put forward by the wali nasab were not in accordance with the teachings of Islamic Shari'a. Finally, based on these considerations in the trial, the judge ruled that the female wali nasab was declared as wali adhal.